2013
DOI: 10.1016/j.jcyt.2012.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Cell therapy with bone marrow stromal cells after intracerebral hemorrhage: impact of platelet-rich plasma scaffolds

Abstract: PRP-derived scaffolds increase the viability and biologic activity of BMSCs and optimize functional recovery when this type of cell therapy is applied after ICH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 38 publications
0
41
0
Order By: Relevance
“…Many stem cell administration routes have been tested, but it remains unclear which is the best option. Findings in ICH model support that cervical vein delivery is inefficient [133] , whereas good outcomes were already observed following stem cell delivery in brain parenchyma [66,111,[113][114][115][116]121,126,[134][135][136][137] , lateral ventricle [120,133] , tail vein [117,119,122,[124][125][126]138,139] , and carotid artery [133,140,141] . However, each one of these alternatives has drawbacks.…”
Section: Preclinical Studies: An Heterogeneous Approach For An Heteromentioning
confidence: 68%
See 3 more Smart Citations
“…Many stem cell administration routes have been tested, but it remains unclear which is the best option. Findings in ICH model support that cervical vein delivery is inefficient [133] , whereas good outcomes were already observed following stem cell delivery in brain parenchyma [66,111,[113][114][115][116]121,126,[134][135][136][137] , lateral ventricle [120,133] , tail vein [117,119,122,[124][125][126]138,139] , and carotid artery [133,140,141] . However, each one of these alternatives has drawbacks.…”
Section: Preclinical Studies: An Heterogeneous Approach For An Heteromentioning
confidence: 68%
“…In late transplantation studies, intracerebral stem cell implantation was performed only two months after ictus. Even so, good functional and morphological outcomes could be observed [111,136] . It is also important to keep in mind that ICH dynamics in rats and humans, as previously discussed, are clearly different in many aspects, including temporality.…”
Section: Preclinical Studies: An Heterogeneous Approach For An Heteromentioning
confidence: 99%
See 2 more Smart Citations
“…The use of PRP as scaffold for the intracerebral administration of bone marrow stem cells resulted in a significant neurologic improvement in experimental animals presenting induced intracerebral hemorrhage. In addition, post-mortem histologic analysis showed that animals that received PRP scaffolds had the stem cells integrated in the injured tissues and presented endogenous neurogenesis, measured by the expression of specific glial proteins and neuronal nucleus [12].…”
Section: Clinical Applications Of Prpmentioning
confidence: 99%